Strategi Public Relations Hotel dalam Membentuk Citra Objek Wisata - Poppy Ruliana; Ririh Dwiantari (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2015)
The purpose of this study is to determine the communication strategy of marketing through public relations approach between hotel and community. The model used in this study is a Public Relations strategy planning model of Cutlip, Center & Broom (2009). Method used in this research is descriptive qualitative approach. Data were collected by doing participatory observation, in-depth interviews, documentary studies and triangulation. Data wrere analyzed through the stages of data reduction, data presentation, conclusion and verification. Result shows that the PR strategy planning model proposed by Cutlip, Center & Broom can support this research.